Child Dietary Diversity, Household Food Insecurity, Child Stunting and Maternal Mental Health Symptoms in Vakinankaratra, Madagascar. (29th May 2020) - Walters, Christine; Komakech, Joel; Rakotomanana, Hasina; Stoecker, Barbara
Abstract: Objectives: This study aimed to determine the association between child dietary diversity, household food insecurity, child stunting, and maternal mental health symptoms in the Vakinankaratra region of Madagascar. Methods: This cross-sectional study included 391 mother-child dyads. The World Health Organization (WHO) standards were used for defining child dietary diversity and child stunting and the Household Food Insecurity Access Scale (HFIAS) was used for food insecurity scores. Maternal symptoms of common mental disorders were assessed using the WHO Self-Reporting Questionnaire (SRQ), which was translated into Malagasy and pre-tested; a cutoff of seven was used to indicate the occurrence of symptoms of common mental disorders. Multivariate linear and logistic regression models adjusted for strata, cluster, and confounding variables were conducted with statistical significance set at P < 0.05. Results: More than half (56.8%) of the mothers reported symptoms of common mental disorders and more than half of the children (69.4%) were stunted. The mean HFIAS score was 10.3 (±5.6) and mean child dietary diversity score was 3.0 (±1.31). Symptoms of common mental disorders were significantly associated with child dietary diversity score in the bivariate analysis but became nonsignificant in the final adjusted model (β = –0.22, P = 0.06, R2 = 0.07). In the adjusted model, having symptoms of common mental disorders was significantly associated with higher HFIAS score (β = 3.45, P < 0.0001, R2 = 0.13) and HFIAS scores were significantly associated with having symptoms of common mental disorders (AOR = 1.31 [1.09–1.17], P < 0.0001). Maternal symptoms of common mental disorders were significantly associated with stunting (AOR = 1.68 [1.02–2.78], P < 0.05). Conclusions: Maternal mental health and household food insecurity were significantly associated in this rural area of the Vakinankaratra region in Madagascar. Furthermore, assessing maternal symptoms of common mental disorders and referring mothers for mental health care appears to be an important consideration for improving child stunting in the region. Funding Sources: Oklahoma State University.